Synthesis and characterization of Schiff base ligand as a carrier and its application for construction of new Mn(II) sensors and their use in petroleum water samples - Tamer Awad Ali; Gehad G. Mohamed (Egyptian Journal of Petroleum)
The ligand (PBABMDP: 2,2′-((1E,1′E)-(1,3-phenylene bis(azanylylidene)) bis(methanyly-lidene))-diphenol was synthesized in a reasonable yield from 2-hydroxybenzaldehyde and m-phenylenediamine and studied using IR, mass, and 1H NMR spectroscopy. PBABMDP has been used as a neutral carrier to make a new carbon paste (CPS) and screen-printed sensors (SPS) that are highly selective to Mn(II) ions. They revealed linear concentration ranges from 1.0 × 10-7 to 1.0 × 10-1 mol L-1 for CPS (sensor I) and from 3.7 × 10-8 to 1.0 × 10-1 mol L-1 for SPS (sensor II), respectively, with Nernstian slopes of 29.01 ± 0.97 and 29.96 ± 0.57 mV decade-1. For sensor I and sensor II, the detection limit, and the response time of the sensors were: 1.0 × 10-7 and 3.7 × 10-8 mol L-1 and 9 and 6 s, respectively. Without observe a divergence, the paste may be used for more than 95 or 182 days and the sensors can be used between 4.0 and 7.5 pH and 3.0 to 8.5 pH. For sensor I and II, the isotherm coefficient of the sensors was 0.000105 and 0.000168 V/oC. The proposed sensors were applied to the determination of Mn(II) ions in real petroleum water samples. The results achieved using this potentiometric method and those obtained with AAS were well agreed.